Third World multinationals : : the rise of foreign investment from developing countries - Wells, Louis T. (Cambridge, Mass.: MIT Press, 1983)
This book explores the question of why firms based in developing countries have chosen to invest in branches, joint ventures, and wholly owned subsidiaries overseas rather than simply export goods or enter into licensing arrangements abroad. In addition to the cost of transport, tariff barriers, and import restrictions, it identifies a number of less apparent factors, such as the motivations of managers in wanting to go abroad, the meshing of technological levels, ethnic ties, and the desire to protect proprietary processes and competitive advantages.
pt. 1. The new multinationals. Terminology -- Data and methodology -- pt. 2. Understanding foreign direct investment. Firm-specific advantages -- Motivations for investment -- Investment or license? -- pt. 3. Small-scale manufacturing as a competitive advantage. Small-scale markets -- Characteristics of the small-scale technology -- Low overheads -- Exploiting the advantages -- pt. 4. Local procurement and special products as competitive advantages. Use of local resources -- Ethnic products -- Other innovations -- Level of technology -- pt. 5. Access to markets as a competitive advantage. Trade name as an advantage -- Following the customer -- The offshore manufacturers -- Price as a marketing tool -- pt. 6. Motivations for foreign investment. Defending export markets -- Quotas and the offshore manufacturers -- The search for lower costs -- Ethnic ties -- Diversification -- Other drives for investment abroad -- Resulting investment patterns -- pt. 7. Invest or license? problems of contract -- Successful contractors -- Partial internalization -- pt. 8. Nonmanufacturing investments. The service sector -- Raw materials -- pt. 9. Government policies. Host governments -- Home governments -- International institutions -- Governments of industrialized countries -- pt. 10. Prospects for the firms. Manufacturing firms -- Nonmanufacturing firms.
Includes index.
Bibliography: p. [193]-200.
Keywords: Corporations -- -- Developing countries; Entreprises mutinationales -- -- Pays en voie de développement.; Corporations -- -- Pays en voie de développement.; Buitenlandse investeringen; Entreprises multinationales -- -- Pays en voie de développement.; Direktinvestition; Investition; Auslandsinvestition; Corporations, Foreign -- -- Developing countries; Investissements étrangers -- -- Pays en voie de développement.; International business enterprises -- -- Developing countries; Internationale ondernemingen; Multinationales Unternehmen; Entwicklungsländer; Developing countries -- -- International business enterprises; Developing countries -- -- Corporations; Foreign investment by multinational companies from developing companies